How to translate the English verb to scan into Italian. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
To translate the English verb to scan into Italian is no easy task, against which all people dealing with a computer measured themselves. It is no easy task because, according to many people, an Italian verb meaning the process of digitizing a paper document through a set called scanner, namely an optical character reader able to transform the image in digital signals, does not exist.